PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN ALAT PERAGA DALAM PENINGKATAN KEMAMPUAN PENALARAN MATEMATIS - Richa Aulya; Jayanti Putri Purwaningrum (JURNAL MathEdu (Mathematic Education Journal), 2021)
In learning mathematics, students' mathematical reasoning ability is important because the learning is more emphasized on a problem-solving and reasoning activity that is very closely related to student achievement. However, in the current condition, students' mathematical reasoning in learning mathematics is still considered lacking and has not been emphasized specifically. The students' low mathematical reasoning needs to be improved in the mathematics learning process. There are several ways to train students in reasoning, namely by using learning models and teaching aids. A learning model that can improve students' mathematical reasoning abilities to make learning situations fun and make students not feel bored is the problem based learning (PBL) learning model. By combining problem based learning models and teaching aids, it can improve students' mathematical abilities so that learning objectives can be achieved and students not only memorize but also understand the subject matter.